Cartier and Islamic art : in search of modernity - Ecker, Heather; Henon-Raynaud, Judith; Possémé, Evelyne; Schleuning, Sarah; Gabet, Olivier; Rainero, Pierre; Lepeu, Pascale; Petit, Violette (Thames & Hudson, 2022)
"A sumptuous exploration of the ways in which the Islamic arts have inspired the famous jewelry house Cartier, this book accompanies a major exhibition at the Musée des Arts Decoratifs, Paris, and the Dallas Museum of Art. Louis Cartier (1875-1942), the grandson of Cartier founder Louis-François, was an impassioned collector and patron of the arts. He was particularly entranced by Islamic arts, especially Persian book arts: their geometric shapes, color combinations, and motifs are apparent in Cartier jewelry to this day. Louis's younger brother Jacques - an expert in precious stones - traveled to India and the Persian Gulf in 1911 and 1912 to experience the culture and bring home treasures of the Middle East: natural pearls. This was the pivotal moment when the dialogue between these two worlds opened up, eventually blossoming into a beautiful relationship that has lasted for decades. Published to accompany a major exhibition at the Musée des Arts Decoratifs in Paris and the Dallas Museum of Art, Cartier and Islamic Arts delves into the Cartier archives to trace the story of Louis Cartier's love of Islamic art and the ways in which he incorporated the Islamic world's stylized motifs into Cartier's jewelry. Dazzling photographs are accompanied by in-depth texts from a raft of distinguished scholars of both Islam and the decorative arts"--